Analisa Limbah Fosfor Kegiatan Keramba Jaring Apung di Danau Laut Tawar Aceh Tengah - Saiful Adhar; Rachmawati Rusydi; Mainisa Mainisa; Erlangga Erlangga; Munawwar Khalil; Eva Ayuzar (Jurnal Serambi Engineering, 2021)
Floating net cage activities can cause  water quality to decrease. The feed remains and the metabolism of the fish  from these activities produces nitrogen and phosphorus .  The objective of this study  is to obtain the calculation model and the amount of phosphorus released into the waters of Laut Tawar Lake  as a result of floating  cage activities. The resulting  formula  was Pw = (F x [P]p) – ((It – Io) x [P]i), where their variables were given feed (F), phosphorus concentration of feed ([P]p), the final weight of fish (It), the initial weight of fish (Io), and phosphorus concentration in fishes ([P]i). It can be used to predict the increase in phosphorus waste based on the increase in floating net cage area. The weight of tilapia increases exponentially with the  day of cultivation in the equation Y = 12.70e0.02x and the goldfish followed the formula  Y = 2.28e0.03x. Phosphorus in tilapia varies  from 1.58% to 2.23% with an average of 1.97%. Goldfish contain  1.19 - 2.02% phosphorus, with an average of 1.52%. Goldfish  growth  was not optimal due to inadequate feeding,   so  without excessive feeding and did not generate  phosphorus waste. The cultivation of  tilapia releases  0.09 Kg P/m2 of phosphorus waste from floating cages .